2013
DOI: 10.1111/codi.12030
|View full text |Cite
|
Sign up to set email alerts
|

Ligation of the intersphincteric fistula tract in low transsphincteric fistulae: a new technique to avoid fistulotomy

Abstract: Low transsphincteric fistulae can be treated successfully by LIFT, without affecting faecal continence. Division of the lower part of the external anal sphincter is no longer necessary in the treatment of low transsphincteric fistulae, which is essential for patients with compromised anal sphincters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 27 publications
1
40
1
3
Order By: Relevance
“…One only compared LIFT with a modification of LIFT, rather than a standard treatment, whilst the other two compared LIFT with a mucosal advancement flap. In addition, 18 case series have been reviewed [187,[190][191][192][193][194][195][196][197][198][199][200][201][202][203][204][205][206] (Table 3). A number of series reporting fewer than 10 patients were disregarded for the purposes of this position statement.…”
Section: Recommendationmentioning
confidence: 99%
“…One only compared LIFT with a modification of LIFT, rather than a standard treatment, whilst the other two compared LIFT with a mucosal advancement flap. In addition, 18 case series have been reviewed [187,[190][191][192][193][194][195][196][197][198][199][200][201][202][203][204][205][206] (Table 3). A number of series reporting fewer than 10 patients were disregarded for the purposes of this position statement.…”
Section: Recommendationmentioning
confidence: 99%
“…Twelve of the 13 studies reported postoperative continence. However, only seven evaluated patients pre-and postoperatively using a validated incontinence score [16,20,[23][24][25][26][27]. In total 183 patients were formally assessed, of whom 11 (6%) had a minor functional disturbance.…”
Section: Continence Disturbancementioning
confidence: 99%
“…The failure rate is approximately 30-60 % for established surgical procedures such as the endorectal advancement flap (ERAF) [3,4] and injection of biological glues [5,6]. Also the initial enthusiasm for even newer techniques, such as anal fistula plug [7,8] and ligation of the intersphincteric fistula tract (LIFT) [9,10], decreased at the long-term follow-up, with a recurrence rate of about 70-80 % and 30-60 %, respectively [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%